2008
DOI: 10.1080/10641734.2008.10505237
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Culture on Perceived Source Credibility of Asian Americans & the Mediating Role of Similarity

Abstract: The current study examines some of the cultural influences for Asian Americans on perceived model credibility. Specifically, the effects of racial congruency and ethnic identification are examined between consumers and ad stimuli as well as the role that similarity plays in the process. The findings reveal that model-consumer racial congruency is an important consideration for enhancing source credibility. However, similarity with the model in terms ofvalues and cultural background was found to mediate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
4

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 48 publications
2
29
1
4
Order By: Relevance
“…For example, in the United States, consumers respond more favourably to models of the same ethnicity (Whittler & DeMeo 1991;Whittler & Spira 2002;Morimoto & La Ferle 2008). When ethnic salience is greater due to a person's minority status, the respondent tends to rate a model of the same ethnicity as more trustworthy, prompting more favourable brand attitudes (Deshpandé & Stayman 1994;Grier & Deshpandé 2001).…”
Section: Model Ethnicity In Asian Marketsmentioning
confidence: 99%
“…For example, in the United States, consumers respond more favourably to models of the same ethnicity (Whittler & DeMeo 1991;Whittler & Spira 2002;Morimoto & La Ferle 2008). When ethnic salience is greater due to a person's minority status, the respondent tends to rate a model of the same ethnicity as more trustworthy, prompting more favourable brand attitudes (Deshpandé & Stayman 1994;Grier & Deshpandé 2001).…”
Section: Model Ethnicity In Asian Marketsmentioning
confidence: 99%
“…In addition, persuasion research has found that the perceived similarity between a message source and recipients in terms of values, attitudes, and/or demographic characteristics affects the persuasiveness of the source (Brock, 1965;Feldman, 1984;Morimoto & La Ferle, 2008;Petty & Wegener, 1998). In particular, Feldman (1984) found evidence on the interaction of perceived similarity with source credibility; high school students tended to adopt nutritional attitudes and behavior when a message was communicated by a source that has high expertise in the issue and shares similar personal characteristics, but they did not show the same degree of acceptance when the message was communicated by a source high in expertise but low in similarity (Feldman, 1984).…”
Section: Moderating Effect Of Value Congruencementioning
confidence: 99%
“…Long afterwards, authors such as Morimoto and La Ferle (2008), Douglas and Craig (2005), and Butt and Run (2012) confirm the ubiquity of the influence of cultural identity and the individuals' relationships with it on most consumer behaviors.…”
Section: Conceptual Framementioning
confidence: 99%